Specific Autobiographical Recall Mediates Impact of Cognition and Depression on Independence Function and Well-Being in Older Adults - Holland, Carol A.; Boukouvalas, Alexis; Clarkesmith, Danielle; Cooke, Richard (Frontiers in Psychology, 2021)
Autobiographical memory specificity has been associated with cognitive function, depression, and independence in older adults. This longitudinal study of 162 older adults moving to active supported living environments tracks changes in the role of the ability to recall specific autobiographical memory as a mediator between underlying cognitive function, or depression, and outcome perceived health or independence (e.g. Instrumental Activities of Daily Living, IADLs), across 18 months, as compared with controls not moving home. Clear improvements across time in autobiographical specificity were seen for residents but not controls, supporting the role of a socially active environment, and confirmed by correlation with number of activities reported in diaries, although the impact of diary activities on the effect of time on autobiographical specificity was not found. The role of autobiographical specificity in mediating general cognition and outcome functional limitations was clear for social limitations at 12 and 18 months, but its role in mediating effects of executive function and perceived health persisted throughout. The role of specificity in mediating between depression and perceived health, IADLs and Functional limitations persisted throughout. Analysis examining autobiographical specificity and depression as joint mediators between cognition and independence showed a forward effect such that higher specificity scores reduced the negative mediation effect of depression on independence. Finally, data showed the reduction of many of these mediations over time, supporting the role of autobiographical memory in times of change in a person’s social situation. Data support potential autobiographical memory intervention development.